2020
DOI: 10.1128/mbio.00485-20
|View full text |Cite
|
Sign up to set email alerts
|

Tombusvirusp19 Captures RNase III-Cleaved Double-Stranded RNAs Formed by Overlapping Sense and Antisense Transcripts in Escherichia coli

Abstract: Antisense transcription is widespread in bacteria. By base pairing with overlapping sense RNAs, antisense RNAs (asRNA) can form double-stranded RNAs (dsRNA), which are cleaved by RNase III, a dsRNA endoribonuclease. The ectopic expression of plant Tombusvirus p19 in Escherichia coli stabilizes ∼21-nucleotide (nt) dsRNA RNase III decay intermediates, which enabled us to characterize otherwise highly unstable asRNA by deep sequencing of p19-captured dsRNA. RNase III-produced small dsRNA were formed at most bacte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 77 publications
3
9
0
Order By: Relevance
“…As we observed a significant reduction in rpoH expression in the rnc mutant during a heat shock, we investigated the importance of RNase III on rpoH mRNA stability after a shift at 45 • C. We observed that RNase III inactivation led to a slight reduction in rpoH stability after a 15 min heat shock from 30 to 45 • C (from 4.01 to 3.39 min, Table 1 and Figure S4A), suggesting that RNase III has only a modest effect on the stability of the rpoH mRNA during a heat shock. However, it should be remembered that the inactivation of RNase III leads to the accumulation of the exoribonuclease PNPase, as previously shown at the mRNA [22] and protein level [23,31]. We observed that the stability of rpoH mRNA after a heat shock in a PNPase inactivated mutant (pnp) is reduced (from 4.01 to 3.14 min, Table 1 and Figure S4A).…”
Section: Rnase III and Pnpase Stabilize Rpoh Mrna During A Heat Shocksupporting
confidence: 77%
See 2 more Smart Citations
“…As we observed a significant reduction in rpoH expression in the rnc mutant during a heat shock, we investigated the importance of RNase III on rpoH mRNA stability after a shift at 45 • C. We observed that RNase III inactivation led to a slight reduction in rpoH stability after a 15 min heat shock from 30 to 45 • C (from 4.01 to 3.39 min, Table 1 and Figure S4A), suggesting that RNase III has only a modest effect on the stability of the rpoH mRNA during a heat shock. However, it should be remembered that the inactivation of RNase III leads to the accumulation of the exoribonuclease PNPase, as previously shown at the mRNA [22] and protein level [23,31]. We observed that the stability of rpoH mRNA after a heat shock in a PNPase inactivated mutant (pnp) is reduced (from 4.01 to 3.14 min, Table 1 and Figure S4A).…”
Section: Rnase III and Pnpase Stabilize Rpoh Mrna During A Heat Shocksupporting
confidence: 77%
“…The transcription of rpoH was shown to be dependent on the sigma factors RpoD, RpoE, RpoN and RpoS and regulated by transcriptional factors DnaA, ZraR, CpxR, IHF, CRP and CytR (Ecocyc database [41]). Remarkably, the details of the transcriptional induction of rpoH during a heat shock remains, to our knowledge, non-elucidated [31]. We compared the induction level of the rpoH mRNA after 15 min heat shock from 30 to 45 • C in mutants inactivated for CRP and/or CytR and/or RNase III.…”
Section: Rnase III Acts Independently From Transcription Factors Crp ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since bacterial genomes are compact and the distance between CDSs is often short, when transcriptional terminator signals between convergent genes are missing and/or transcriptional read-through occurs, long antisense overlapping 3′UTRs are produced (Hernández et al, 2006 ; Toledo-Arana et al, 2009 ; Arnvig et al, 2011 ; Lasa et al, 2011 ; Nicolas et al, 2012 ; Moody et al, 2013 ; Mäder et al, 2016 ; Stazic and Voss, 2016 ; Bidnenko et al, 2017 ; Huang et al, 2020 ; Toledo-Arana and Lasa, 2020 ) ( Figure 1A ). In addition, more complex transcriptional organizations like operons containing a gene(s) that is transcribed in the opposite direction to the rest of the operon are also known for generating long overlapping transcripts (Lasa et al, 2011 ; Sáenz-Lahoya et al, 2019 ).…”
Section: Bacterial 3′utrs Are Longer Than Previously Expectedmentioning
confidence: 99%
“…In addition, more complex transcriptional organizations like operons containing a gene(s) that is transcribed in the opposite direction to the rest of the operon are also known for generating long overlapping transcripts (Lasa et al, 2011 ; Sáenz-Lahoya et al, 2019 ). The outcome is usually the development of large double-stranded RNA regions that are processed by RNase III in both Gram-positive and Gram-negative bacteria (Lasa et al, 2011 , 2012 ; Gatewood et al, 2012 ; Lioliou et al, 2012 ; Lybecker et al, 2014 ; Huang et al, 2020 ). Interestingly, overlapping 3′UTRs are widely distributed in bacteria and constitute an abundant source of antisense RNAs (Arnvig et al, 2011 ; Lasa et al, 2011 ; Ruiz de Los Mozos et al, 2013 ).…”
Section: Bacterial 3′utrs Are Longer Than Previously Expectedmentioning
confidence: 99%